ANALISIS ISI PESAN AKHLAK KHADIJAH DENGAN MENGGUNAKAN PENDEKATAN PSIKOANALISIS DALAM NOVEL KHADIJAH “KETIKA RAHASIA MIM TERSINGKAP” - Nita Puspitasari; Ridwan Abdurahman; Latifah Latifah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the limited Khadijah novel "When the Secrets of the Unveiled Mim" by Sibel Eraslan are rich in motivation that reviews the story of a Khadijah whose noble character is good, his character looks beautiful in his face. The formulation of the problem from this study is that with the lives of women today, it can be said that there is less motivation for motivation in terms of morals and morals. This study aims to describe and explain the motivation drive in terms of morals and morals that Khadijah has. This study used descriptive qualitative research using content analysis. The researcher used the method of psychoanalytic study which focused on the unconscious world and was not limited to the world of the conscious mind. Documents in Khadijah's novel research "When Mim Secrets Revealed" by Sibel Eraslen. The results of the study show that a noble Khadijah who has a beautiful face and behaves well which makes the dream of all men start from a heart that is clean of various liver diseases that damage it.